2007
DOI: 10.5271/sjweh.1112
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant populations, work and health—a systematic literature review

Abstract: Scand J Work Environ Health 2007;33(2):96-104 that can encourage immigration, there is an important connection to be made between migrating populations, work, and the effect that both foreign status and worker status have on the health and quality of life of these groups. It is probable that these newly arrived persons find themselves in positions of special occupational vulnerability, with high levels of precarious employment and poor work conditions.Considering the magnitude of current human movement, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
155
0
20

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(191 citation statements)
references
References 53 publications
13
155
0
20
Order By: Relevance
“…To date, most research in this area has focused on Western cultural contexts where there have been active migrations over the past decades (e.g., Mirdal, 1985;Weishaar, 2008Weishaar, , 2010. Moreover, it has been suggested that migrants' acculturation and their mental health affect their economic conditions and activities (Bhui et al, 2003;Moussaoui & Agoub, 2010); however, relatively few studies have focused on migrants' job stress, job adjustment and their mental health (Ahonen, Benavides, & Benach, 2007;de Castro, Gee, & Takeuchi, 2008).…”
Section: Migrant Workers' Double Burden: Job Adaptation and Acculturamentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most research in this area has focused on Western cultural contexts where there have been active migrations over the past decades (e.g., Mirdal, 1985;Weishaar, 2008Weishaar, , 2010. Moreover, it has been suggested that migrants' acculturation and their mental health affect their economic conditions and activities (Bhui et al, 2003;Moussaoui & Agoub, 2010); however, relatively few studies have focused on migrants' job stress, job adjustment and their mental health (Ahonen, Benavides, & Benach, 2007;de Castro, Gee, & Takeuchi, 2008).…”
Section: Migrant Workers' Double Burden: Job Adaptation and Acculturamentioning
confidence: 99%
“…Among the few of studies on migrant workers, Ahonen et al (2007) suggests that a lack of understanding of work and safety caused by language barriers as well as mental health problems due to homesickness and difficulty in relationship formation are major acculturation issues. However, as the authors note, most of these studies have focused on unskilled workers in the U.S.…”
Section: Migrant Workers' Double Burden: Job Adaptation and Acculturamentioning
confidence: 99%
“…Tendo em conta a centralidade do trabalho para os fenômenos migratórios, e que muitos haitianos vieram ao Brasil na expectativa de conseguir trabalho 5 , essa situação pode levar à percepção da piora na saúde e distúrbios mentais, conforme vem sendo mostrado em pesquisas de diversos contextos mundiais 6,7 .…”
Section: Discussionunclassified
“…O relato de dores no corpo e cansaço pode estar relacionado à carga horária, além da exigência física e riscos percebidos, que interatuam com o corpo dos trabalhadores e geram perda das capacidades corporais e psíquicas 8 . Pesquisas apontam problemas de saúde mental em trabalhadores migrantes, como casos de depressão ocasionados pela "solidão aliada à longa e exaustiva jornada de trabalho", silêncio sobre o adoecer e o medo de perder o emprego e não conseguir se manter longe de casa 6,7,9 .…”
Section: Discussionunclassified
“…OFWs' primary reason for working abroad is the desire to escape poverty or to achieve socioeconomic mobility, mainly for their family, rather than individual aspirations [19,20]. However, while abroad, and similarly to other labor migrants, OFWs are at higher risk of experiencing mental health-related issues such as loneliness, stress, anxiety, depression, and serious mental illness [20,21], and for experiencing occupational hazards [22]. Resolving these challenges are problematic, however, as labor migrants tend to have poor access to mental health services [23][24][25] and poor support systems [26].…”
Section: Introductionmentioning
confidence: 99%